Reemergence of human malaria in Atlantic Forest of Rio Grande do Sul, Brazil - Alessandra Bittencourt de Lemos; Onilda Santos da Silva; Sandra Cristina Deboni; Valdir Schallemberger; Edmilson dos Santos; Marco Antônio Barreto de Almeida; Anne Andrea Dockhorn Marth; Sidnei Silva; Aline Rosa de Lavigne Mello; Teresa Fernandes Silva-do-Nascimento; Maria de Fátima Ferreira‐da‐Cruz; Ricardo Lourenço‐de‐Oliveira; et al. (2022)
Unforeseen Plasmodium infections in the Atlantic Forest of Brazilian Extra-Amazonian region could jeopardise malaria elimination. A human malaria case was registered in Três Forquilhas, in the Atlantic Forest biome of Rio Grande do Sul, after a 45 years’ time-lapsed without any malaria autochthonous notification in this southern Brazilian state. This finding represents the expansion of the malaria distribution areas in Brazil and the southernmost human malaria case record in South America in this decade. The coexistence of the bromeliad-breeding vector Anopheles (Kerteszia) cruzii and non-human primates in the Atlantic Forest regularly visited by the patient claimed for the zoonotic origin of this infection. The reemergence of Atlantic Forest human malaria in Rio Grande do Sul was also discussed.